PERANCANGAN SISTEM BOOKING TRUK RODA 6 BERBASIS ANDROID - Putra, Dedi; Batubara, M.Diarmansyah (Sisfokomtek, 2020)
A truck is a large car with a large tailgate usually used to transport goods and is generally used by companies or individuals to carry goods to achieve a predetermined destination. Because there are still many companies or individuals who want to use transportation services often have difficulty in finding transportation, especially wheel transportation 6. Many companies provide transportation services, both transportation of goods and moving. But until now there has been no company that provides freight or moving services that can be ordered online like other means of transportation that can be ordered anytime and anywhere. In this study the authors designed a 6-wheeled truck fleet booking application that can be ordered using a smartphone. The application is designed using the Java programming language and uses Android Studio. With this application it will make it easier for companies or individuals to get trucks directly because it can be ordered anytime and anywhere.